2010
DOI: 10.2202/1948-4682.1089
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Disparity in Access to Organ Transplant in the United States and Other Western Countries: A Prolegomenon to A Solution

Abstract: Background: Disparities in access to and in outcome of organ transplantation are widely discussed topics among transplant researchers in many Western countries. Among various types of disparities examined in existing studies, “geographic disparity,” i.e., disparity due to a recipient's location, is most common. Despite a number of articles that acknowledge the existence of geographic disparities, the literature has been relatively silent about the historical and international efforts to address these issues. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Interventions such as patient navigation (Freeman, 2006) that help disadvantaged patients navigate the barriers to seeking treatment for chronic illnesses such as cancer is one example of such an intervention, and may be a way to address other health care disparities through informational and instrumental social support. This study also has international implications for further research, as kidney transplant racial disparities exist in Canada (Yeates et al, 2004), Australia (Cass, Cunningham, Snelling, Wang, & Hoy, 2003), France, Spain, and the United Kingdom (Koizumi, 2010). Considering dialysis patients’ social milieu can be complementary to the existing research regarding kidney transplant disparity in the United States and beyond.…”
Section: Discussionmentioning
confidence: 93%
“…Interventions such as patient navigation (Freeman, 2006) that help disadvantaged patients navigate the barriers to seeking treatment for chronic illnesses such as cancer is one example of such an intervention, and may be a way to address other health care disparities through informational and instrumental social support. This study also has international implications for further research, as kidney transplant racial disparities exist in Canada (Yeates et al, 2004), Australia (Cass, Cunningham, Snelling, Wang, & Hoy, 2003), France, Spain, and the United Kingdom (Koizumi, 2010). Considering dialysis patients’ social milieu can be complementary to the existing research regarding kidney transplant disparity in the United States and beyond.…”
Section: Discussionmentioning
confidence: 93%
“…A number of factors contribute to these discrepancies, including regional differences in the supply and demand for donor organs [8], centers' organ acceptance practices [8], the geographical boundaries of UNOS transplant regions and donor service areas (DSA) within them [9,10], and the size and characteristics of the potential donor populations [8].…”
Section: The Current Situation: Geographic Disparitiesmentioning
confidence: 99%
“…Studies from across the world have found that access to transplant centers, the likelihood of being listed, and transplant outcomes are not equitable across all geographic areas. [12][13][14][15][16][17][18][19] However, social determinants of health (SDOH), which also vary by location, have not been widely studied in relation to transplant. SDOH include income, educational level, physical environment, social support, and access to quality healthcare services have each been demonstrated to significantly impact patients' health and response to medical treatment in multiple areas of medicine.…”
Section: Introductionmentioning
confidence: 99%